Modelling runoff and erosion, and their mitigation, in burned Portuguese forest using the revised Morgan-Morgan-Finney model - Vieira, D. C. S.
The revised Morgan-Morgan-Finney (MMF) model was used as a modelling approach, which has performed reasonably well to estimate soil losses for burned areas in humid Mediterranean forests in Portugal, and NW Spain. Simple model enhancement approaches are applied to recently burned pine and eucalypt forested areas in north-central Portugal and to subsequent post-wildfire rehabilitation treatments. Model enhancement is validated by applying it to another similar burned area to evaluate model calibration robustness and wider applicability. Model modifications involved: (1) focusing on intra-annual changes in parameters to incorporate seasonal differences in runoff and erosion; and (2) inclusion of soil water repellency in runoff predictions. The main results were that following wildfire and mulching in the plantations: (1) the revised model was able to predict first-year post-fire plot-scale runoff and erosion rates (NS(Runoff)=0.54 and NS(Erosion)=0.55) for both forest types, and (2) first year predictions were improved both by the seasonal changes in the model parameters (NS(Runoff)=0.70 and NS(Erosion)=0.83); and by considering the effect of soil water repellency on the runoff (NS(Runoff)=0.81 and NS(Erosion)=0.89), (3) the individual seasonal predictions were considered accurate (NS(Runoff)=0.53 and NS(Erosion)=0.71), and the inclusion of the soil water repellency in the model also improved the model at this base (NS(Runoff)=0.72 and NS(Erosion)=0.74). The revised MMF model proved capable of providing a simple set of criteria for management decisions about runoff and erosion mitigation measures in burned areas. The erosion predictions at the validation sites attested both to the robustness of the model and of the calibration parameters, suggesting a potential wider application.